The Historicity of Ratib Al-Haddad Tradition and Its Relevance of Priority In The Covid-19 Pandemic - Moh. Ashif Fuadi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
One of the most popular wirid in Indonesia is Ratib al-Haddad. The practice is a collection of prayers arrangedby Abdullah ibn Alawi al-Haddad taken of the Qur'an and hadith. In a pandemic situation, the practicebecomes one that is recommended by some circles to be beread so that the pandemic outbreak immediately subsides.But many of the practitioners are not yet aware of its history and virtues, especially during the pandemic. Thispaper intends to study the history of the wirid from the beginning of writing and its virtues. Through the historicalapproach, the method literature review, and observation of the practice of the ratiban tradition, this paper willexplain the historical studies and benefits of practicing wirid Ratib al-Haddad, which is sourced from thedescription of the book of syarah (explanatory) of the Ulama. The wirid was compiled by al-Haddad to avoid thechaos of akidah there was that time. In addition, there are eight virtues implied in the text wirid one of whichavoids the outbreak so that no doubt if the practice is widely recommended and practiced in the current situation ofthe Covid-19 pandemic. The influence of ratib al-Haddad practice can also be seen through the congregation of theMajelis Jum'at Pagi (MJP) Al-Khoirot, who stated more peace of mind after practicing the wirid so as to increaseimmunity.